Supply chain strategy and performance: Mediating effect of supply chain practices - Othman, Abdul Aziz; Yusoff, Rushami Zien; Ismail, Mohd Azril; Husin, Rohana (2012)
This article reports a study designed to explore the state of supply chain practices in Malaysian Automotive industry by examining the mediating effect of supply chain practice between supply chain strategy and supply chain performance. This study is accomplished by using survey questionnaire that was answered by 65 respondents from Malaysian automotive components manufacturing firms.The study found that supply chain strategy had no direct relationship with supply chain performance, but was mediated by supply chain practices.This also found that the supply chain practices act as full mediator towards relationship between supply chain strategy and performance.